2010
DOI: 10.1093/hmg/ddq411
|View full text |Cite
|
Sign up to set email alerts
|

Measurement methods and accuracy in copy number variation: failure to replicate associations of beta-defensin copy number with Crohn's disease

Abstract: The copy number variation in beta-defensin genes on human chromosome 8 has been proposed to underlie susceptibility to inflammatory disorders, but presents considerable challenges for accurate typing on the scale required for adequately powered case-control studies. In this work, we have used accurate methods of copy number typing based on the paralogue ratio test (PRT) to assess beta-defensin copy number in more than 1500 UK DNA samples including more than 1000 cases of Crohn's disease. A subset of 625 sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
118
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(120 citation statements)
references
References 31 publications
2
118
0
Order By: Relevance
“…The copy number is reflected in mRNA expression levels, and Crohn's disease has been associated with both a decreased copy number of DEFB4 and a decreased intestinal mRNA expression of HBD2 (Fellermann et al 2006). A more recent study has failed to replicate these findings (Aldhous et al 2010), and copy number polymorphisms are not associated with severity of lung disease in cystic fibrosis (Hollox et al 2005). It remains to be observed whether the copy number correlates with other infectious or inflammatory conditions.…”
Section: Defensinsmentioning
confidence: 94%
“…The copy number is reflected in mRNA expression levels, and Crohn's disease has been associated with both a decreased copy number of DEFB4 and a decreased intestinal mRNA expression of HBD2 (Fellermann et al 2006). A more recent study has failed to replicate these findings (Aldhous et al 2010), and copy number polymorphisms are not associated with severity of lung disease in cystic fibrosis (Hollox et al 2005). It remains to be observed whether the copy number correlates with other infectious or inflammatory conditions.…”
Section: Defensinsmentioning
confidence: 94%
“…A link between copy number and disease has been reported, where an increase in copy number is associated with an increased risk of psoriasis [15]. A link between copy number and Crohn’s disease has also been reported but the copy number associations are confusing and technically challenging, with different populations having a reduced [16] or increased [17] association, or none at all [18]. Polymorphisms in the promoter of DEFB1 (which is not a copy number variable) have also been associated with Crohn’s disease [19].…”
Section: Introductionmentioning
confidence: 99%
“…25 The results of Aldhous et al support this observation; in spite of a large sample size, they failed to replicate both the previously reported high and low genomic copy numbers of DEFB4 among patients with Crohn's disease. 19,26,27 In addition, discrepancies in assay reliability could play a role in explaining differences in the obtained results as well as the difference between the paralog ratio test used in the Korean study and the quantitative PCR assay used in the present study. 24 However, Fernandez-Jimenez et al demonstrated that both techniques can produce comparable DEFB4 results with the use of optimum DNA normalisation and high-quality genomic DNA.…”
Section: Discussionmentioning
confidence: 83%